1978
DOI: 10.1104/pp.62.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Solubilized Microsomal Auxin-binding Protein from Coleoptiles and Primary Leaves of Zea mays

Abstract: An auxln-blndng protein can be soh_Ilize from microsoml anes of Zes mays using either Triton X-100 extraction of the mmbranes or buffer extraction of the acetone-precipitated membranes. This paper describes the properties of the biding protein so ld by thes two methods. The bndng is assayed by gel filtration chromatography in the presence of napbthalene 12-i4CIacetlc acid. Bing is rapid and reversible with an optium at pH 5. Both preparations show similar molecular weights by gel filtratio (80,000 daons) at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The NAA-binding system of maize coleoptile was chosen for the assay because it has been well characterized by Ray et al (22). We show here that 4-, 5-, and 6-N3IAA bind reversibly in the dark and that, on photolysis, 5 binding is a modification of the method of Ray et al (22) and is similar to the assay used to measure IAA uptake in zucchini vesicles (10). The modifications shorten the time, increase the number of samples that can be processed at once, and allow the use of a high speed centrifuge in place of an ultracentrifuge.…”
mentioning
confidence: 66%
“…The NAA-binding system of maize coleoptile was chosen for the assay because it has been well characterized by Ray et al (22). We show here that 4-, 5-, and 6-N3IAA bind reversibly in the dark and that, on photolysis, 5 binding is a modification of the method of Ray et al (22) and is similar to the assay used to measure IAA uptake in zucchini vesicles (10). The modifications shorten the time, increase the number of samples that can be processed at once, and allow the use of a high speed centrifuge in place of an ultracentrifuge.…”
mentioning
confidence: 66%
“…4). This result suggests that the auxin efflux carrier was not being labeled, since TIBA has been shown to specifically inhibit auxin association with this site in vivo (4) and in vitro (5,28 (29), 40 kDa (30), and 20 kDa (31-33) have been isolated, some of which (31,32) appear to be of PM origin. It is possible that these polypeptides are related to one another as monomers of a multimeric protein, and the sizes might suggest that they are related to our polypeptides as well.…”
Section: Resultsmentioning
confidence: 99%
“…The proteic nature of the sites has been demonstrated (6,19) and previous attempts have been made to determine some of the amino acid residues, essential for auxin binding (6,19,29). It has been reported that at least one cysteinyl residue is likely to play a prominent role in the binding site (6,29). Other data (10, 19) suggest the presence ofan essential reducible group, possibly a disulfide.…”
mentioning
confidence: 95%
“…Since the specificity of the sites is in rather good agreement with the specificity of the coleoptile straight growth test, it has been suggested that these binding sites might represent receptors involved in the in vivo auxin action (20). The proteic nature of the sites has been demonstrated (6,19) and previous attempts have been made to determine some of the amino acid residues, essential for auxin binding (6,19,29). It has been reported that at least one cysteinyl residue is likely to play a prominent role in the binding site (6,29).…”
mentioning
confidence: 99%